All Are Neighbors - Penfold, Alexandra; Kaufman, Suzanne (New York : Alfred A. Knopf, 2022)
"When a new family moves in, the whole neighborhood comes together to celebrate what makes their community diverse and special"--.
new kids book 2022 fall.
Ages 4-8.
Grades K-1.
Keywords: Stories in rhyme; Communities -- Fiction; Neighbors -- Fiction; Stories in rhyme; Picture books